Development Strategy of Arabic Language Education Program through Alumni Penetration in East Kalimantan Madrasah - Abusyairi, Khairy; Syarifaturrahmatullah, Syarifaturrahmatullah; Hidayat, Ahmad Fadhel Syakir; Wardhana, Kautsar Eka (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeru Sultan Aji Muhammad Idris Samarinda, 2024)
The aim of this research is to determine the employment rate of Arabic language education graduates in Madrasas across East Kalimantan and to understand the trending profiles that the job market seeks from graduates of the Arabic language education program in East Kalimantan. The research employs a mixed methods approach. The study's population includes all Madrasas in East Kalimantan, encompassing both Madrasah Ibtidiyah, Madrasah Tsanawiyah, and Madrasah Aliyah. This research was conducted in the Arabic language education program of the Faculty of Tarbiyah and Education Sciences, as well as the Madrasas located throughout East Kalimantan, ranging from primary (MI) and middle (MTs) schools to high schools (MA), both public and private. The research was carried out in nine different areas: Samarinda, Balikpapan, Penajam Paser Utara (PPU), Paser (Tanah Grogot), Kutai Kartanegara (Tenggarong), Kutai Barat (Melak), Berau, Bontang, and Kutai Timur (Sangata). The research findings reveal the following the percentage of employment of graduates from the Arabic language education program at FTIK UINSI Samarinda in Madrasas across East Kalimantan is minimal, at approximately 17%. Some teachers responsible for teaching Arabic language subjects are graduates of Islamic Religious Education (PAI).